Grenada. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Granada during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as financing, leadership, trade, export, safety, import, production, organic agriculture, quality control, use of organic fertilizers and production of cocoa, eggs and meat.